2015
DOI: 10.1002/rnj.201
|View full text |Cite
|
Sign up to set email alerts
|

An Educational Intervention to Increase Nurse Adherence in Eliciting Patient Daily Goals

Abstract: Background: The literature suggests that nurse and patient collaborative goal setting demonstrates better patient outcomes. The SMART goal evaluation method (Specific, Measureable, Attainable, Relevant, and Timely) is a strategy to develop effective and measureable goals. Purpose: The purpose of this educational project was to improve nurse collaborative goal-setting skills. Methods: A pre-and postevaluation of an educational intervention was accomplished by patient interviews and observation for adherence to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 12 publications
0
33
0
Order By: Relevance
“…We further applied specific, measurable, attainable, realistic, and time-sensitive goal setting for patients, which fostered more effective evidence-based patient counseling. 19 The user guide for charting in the EMR and the presence of more student-informaticists on site increased the accuracy and efficiency of medical charting. An EMR user guide is usually available in clinics, especially after a new EMR system is implemented.…”
Section: Discussionmentioning
confidence: 99%
“…We further applied specific, measurable, attainable, realistic, and time-sensitive goal setting for patients, which fostered more effective evidence-based patient counseling. 19 The user guide for charting in the EMR and the presence of more student-informaticists on site increased the accuracy and efficiency of medical charting. An EMR user guide is usually available in clinics, especially after a new EMR system is implemented.…”
Section: Discussionmentioning
confidence: 99%
“…These results were similar to Revello and Fields findings of increased whiteboard documentation and increased patient perception of goal collaboration after a nurse education intervention. 18 Consistency in the educational intervention allowed for a framework and reminder to nurses to elicit patient goals.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, this study showed that the nurse educational intervention increased whiteboard documentation, articulation of goals, nurse collaboration concerning goals and patients felt more informed by nurses. 18 Although daily goals are addressed in the literature, this search revealed that many studies look at daily goals through the perspective of the interprofessional team rather than the patient. This project examined the impact of nurse prompts on documentation of goals and also measured the patient perspective of daily goals, nurse satisfaction, and perceived barriers to eliciting goals.…”
Section: Review Of Literaturementioning
confidence: 99%
See 2 more Smart Citations